Implementation of JKN Mobile Application-Based Health Services in Reducing Queues at the Karang Anyer Health Center Beringin District Deli Serdang Regency - Nainggolan, Fikriyah Arfina; Anna Tirawani Ambarita; Agustatius Sitepu; Keleng Ate Ginting; Layari Tarigan (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
The JKN mobile application is a digital transformation of the BPJS health business model which originally consisted of administrative activities carried out at branch offices or health facilities. Now, participants can use this application wherever and whenever they want (self service). By using the JKN mobile application, the public and participants can obtain many conveniences, such as ease of paying and changing membership data, ease of accessing information about family participant data. The aim of this research is to implement health services based on the JKN mobile application to reduce queues at the Karang Anyer Health Center. The type of research taken is qualitative research. The subjects in this study were 5 people. Meanwhile, data collection techniques use observation, interview and documentation techniques. The research results show that the National Health Insurance (JKN) mobile application at the Karang Anyer Community Health Center is very effective and efficient in helping patients with registration, referrals and doctor consultations at the Community Health Center. Conclusion By using this application, patients can speed up the registration and referral process and get information more quickly. Patients can also make direct referrals to specialist facilities, which saves time and speeds up the service process. The JKN mobile application for doctor consultations can also be accessed directly by patients via the application. This helps doctors plan their schedules better.